Statistics and Calculation of Entropy of Dominating David Derived Networks. (1st July 2021) - Zhao, Xuemei; Ali, Haidar; Ali, Bilal; Binyamin, Muhammad Ahsan; Liu, Jia-Bao; Raza, Ali
Abstract : A graph's entropy is a functional one, based on both the graph itself and the distribution of probability on its vertex set. In the theory of information, graph entropy has its origins. Dominating David derived networks have a variety of important applications in medication store, hardware, and system administration. In this study, we discuss dominating David derived network of type 1, 2, and 3 written as D 1 n, D 2 n, and D 3 n, respectively of order n . We also compute some degree-based entropies such as Randić, A B C, and GA entropy of D 1 n, D 2 n, and D 3 n .